Local attributable burden disease to PM2.5 ambient air pollution in Medellín, Colombia, 2010–2016 [version 1; peer review: 2 approved] - Hugo Grisales-Romero (F1000 Research Ltd, 2021)
Background: Exposure to 2.5-micron diameter air pollutants (PM2.5) has been associated with an increased risk of illness and death worldwide; however, in Latin American health impacts assessment of this risk factor is scarce. Medellín is one of the most polluted cities in the region, with a population growth rate that is twice as high as that of other Colombian cities, which implies a growing population at risk. Methods: A descriptive study of the disease burden was carried out using the city as the unit of observation. Health events were selected based on epidemiologic evidence and the availability of the population attributable fraction associated with PM2.5. The mortality records were taken from the module of deceased of the Single Registry of Affiliates of the Health System; the morbidity records were taken from the Individual Health Services Registries. For the estimation of the burden of disease, the current Global Burden of Disease guidelines were followed. Results: Attributable disability-adjusted life years to exposure to ambient PM2.5 pollution (DALYsPM2.5) constituted 13.8% of total burden of the city. Males showed the greatest loss of DALYsPM2.5 due to acute events, while in women the greatest loss was due to chronic events. Ischemic heart disease, chronic diseases of the lower respiratory tract, and influenza and pneumonia were the events that contributed the most to DALYsPM2.5. 71.4% of the DALYsPM2.5 corresponded to mortality, mainly in the population over 65 years of age. Regarding attributable morbidity, acute events were more prevalent in both sexes, especially due to respiratory diseases Conclusion: Premature death among the elderly population has the greatest weight on burden of disease attributable to ambient PM2.5 pollution, mainly due to respiratory and cardiovascular diseases, without significant differences according to gender.